Dog owners’ perspectives on canine heart disease in Klang Valley, Malaysia - Noordin, Norhidayah; Khor, Kuan Hua; Khor, Kuan Siew; Lim, Yi Jun; Lee, Yong Chong (MDPI, 2022)
Canine heart disease often requires long-term treatment, which involves a continuous commitment from the dog owners. In addition to investigating their awareness and knowledge, the Theory of Planned Behavior was applied to also analyze attitude, subjective norm, and perceived behavioral control (PBC) of the dog owners, with empathic concern as a moderator in predicting intention to treat canine heart disease. Through a convenience sampling approach, 261 respondents, who were clients of University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM), with experience in owning or caring for dogs, were recruited. While the majority of the respondents (83.5%) claimed that they were aware of canine heart disease, most respondents (45.6%) could only identify 5 to 8 (Fair) out of 12 of the salient clinical signs. Most dog owners (92.3%) were willing to seek treatment if the pet dogs were affected, although the intent is deterred by cost (39.5%). In this study, attitude, subjective norms, and perceived behavioral control were significant predictors for the intention to treat. Dog owners with low empathic concern can be motivated to treat affected dogs by cultivating perceived behavioral control. Therefore, continual education may improve dog owners’ preconceived ability to provide care, and veterinarians may play an important role to encourage treatment in dogs diagnosed with heart disease.